log 4^(x - 1) = log 7
(x - 1) log 4 = log 7
x - 1 = log 7 / log 4
x = 1 + ( log 7 / log 4 )
Note
log can be to any base.
2007-10-23 19:54:25
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
Take the log of both sides; since the (x-1) is an exponent it becomes multiply:
(x-1) log 4 = log 7
Now using your calculator, divide log 7 by log 4, which would equal (x-1), then add 1
2007-10-23 13:51:42
·
answer #2
·
answered by hayharbr 7
·
0⤊
0⤋
x=3
2007-10-23 13:49:11
·
answer #3
·
answered by Bing Bong Bao 3
·
0⤊
2⤋
(x-1) * log 4 = log 7
x = log 7 / log 4 + 1
x= 2.4036
2007-10-23 13:51:27
·
answer #4
·
answered by tanzer360 5
·
0⤊
0⤋
is that 4 raised to the (x-1)power or 4 multiplied by (x-1) If you add this information I will gladly answer the question
2007-10-23 13:52:21
·
answer #5
·
answered by ws 3
·
0⤊
0⤋
x = 1 + log_base_4(7) = 1 + ln(7)/ln(4)
2007-10-23 13:50:39
·
answer #6
·
answered by Alina 2
·
0⤊
0⤋
4^(x-1) = 7, so
ln 7 = (x-1) ln 4
x-1 = ln 7/ln 4 = 1.4037 (approx.)
x = 2.4037
2007-10-23 13:52:06
·
answer #7
·
answered by Mark H 3
·
0⤊
0⤋
Kirk to Enterprise
2007-10-23 13:50:27
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
4^(x-1) = 7
LN4^(x-1) = (x-1)LN4 = LN7
x = LN7/LN4 +1 = 2.403677
2007-10-23 13:51:03
·
answer #9
·
answered by fcas80 7
·
0⤊
0⤋
sori not so good in maths
2007-10-23 13:49:56
·
answer #10
·
answered by Perfectionist 6
·
0⤊
1⤋